Targeted hyperalkalization with NaOH-loaded starch implants enhances doxorubicin efficacy in tumor treatment - Changkyu Lee (Asian Journal of Pharmaceutical Sciences, 2023)
High-alkali treatment using sodium hydroxide (NaOH) injection can be a therapeutic approach for killing tumor cells. Alkalization can damage cellular structures and lead to cell death. Increased alkalinity can also enhance the efficacy of certain chemotherapeutic drugs such as doxorubicin (DOX). In this study, NaOH-loaded starch implants (NST implants) were used to induce hyperalkalization (increase pH) in the tumor environment, thereby inducing necrosis and enhancing the effects of DOX. NaOH is a strongly alkaline substance that can increase the pH when injected into a tumor. However, the administration of NaOH can have toxic side effects because it increases the pH of the entire body, not just at the tumor site. To overcome this problem, we developed an injectable NST implant, in which NaOH can be delivered directly into the tumor. This study showed that NST implants could be easily administered intratumorally in mice bearing 4T1 tumors and that most of the NaOH released from the NST implants was delivered to the tumors. Although some NaOH from NST implants can be systemically absorbed, it is neutralized by the body's buffering effect, thereby reducing the risk of toxicity. This study also confirmed both in vitro and in vivo that DOX is more effective at killing 4T1 cells when alkalized. It has been shown that administration of DOX after injection of an NST implant can kill most tumors. Systemic absorption and side effects can be reduced using an NST implant to deliver NaOH to the tumor. In addition, alkalinization induced by NST implants not only exerts anticancer effects but can also enhance the effect of DOX in killing cancer cells. Therefore, the combination of NaOH-loaded starch implants and DOX treatment has the potential to be a novel therapy for tumors.